2018
DOI: 10.1021/acs.jproteome.7b00828
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Interferon-Induced Proteins with Tetratricopeptide Repeats as Markers of M1 Macrophage Polarization

Abstract: Macrophages, which accumulate in tissues during inflammation, may be polarized toward pro-inflammatory (M1) or tissue reparative (M2) phenotypes. The balance between these phenotypes can have a substantial influence on the outcome of inflammatory diseases such as atherosclerosis. Improved biomarkers of M1 and M2 macrophages would be beneficial for research, diagnosis, and monitoring the effects of trial therapeutics in such diseases. To identify novel biomarkers, we have characterized the global proteomes of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 66 publications
(115 reference statements)
3
36
0
Order By: Relevance
“…(2.7-fold) (12); while M2 markers included TGM2 (28-fold) (30) and CD209 (2.3-fold) (31). In addition, the over-expression of LSP1 (5-fold) was also detected in M2 type, which is consistent with a previous study (12).…”
Section: Polarization Of Human Thp-1 and Mouse Raw2647 Cell Lines Into M1 And M2 Macrophagessupporting
confidence: 90%
“…(2.7-fold) (12); while M2 markers included TGM2 (28-fold) (30) and CD209 (2.3-fold) (31). In addition, the over-expression of LSP1 (5-fold) was also detected in M2 type, which is consistent with a previous study (12).…”
Section: Polarization Of Human Thp-1 and Mouse Raw2647 Cell Lines Into M1 And M2 Macrophagessupporting
confidence: 90%
“…The rst subpopulation, C0_MHCII hi -CXCL2, characterised by Cxcl2, N l3 and Osm, had the phenotype of activated macrophages 38,39,40 . The second subpopulation showed signi cant expressions of I t3b, I t3 and I t2, typical of polarised M1 macrophages 41 , suggesting proin ammatory function. In addition, this subpopulation also showed signi cant upregulation of several other interferon-induced protein relevant genes, thus we labelled it as C1_MHCII hi -IFIT.…”
Section: Resultsmentioning
confidence: 95%
“…Further analysis using a Kaplan-Meier curve and Log-rank test revealed that all top 5 hub genes, except CCL5, influenced the RFS of patients with CRC. IRF1, which belongs to the IRF family (34), is weakly expressed in resting dendritic cells and macrophages, but is induced by interferon-γ (IFN-γ) in M1 polarized macrophages (35,36). Previous studies have revealed that IRF1 inhibited the proliferation and metastasis of CRC (37,38).…”
Section: Discussionmentioning
confidence: 99%